Psychosocial and quality of life assessment in cancer patients: a pilot study in Indian set up - Chaudhuri, Santanu; Gupta, Sanjeev K.; Panda, Debashis; Kumar, Navin; Kumar, Neeraj; Ganpathi, Vani; Vishwakarma, Pushpanjali; Sharma, Mamta (International Journal of Research in Medical Sciences, 2019)
Background: Routine screening for distress is internationally recommended as a standard of care among cancer patients. This study was conducted to assess the level of stress and determine the association between quality of life (QOL) with demographic, socio-economic status, treatment phase, cancer stage, etc. Methods: An observational study, performed in the department of Clinical Oncology, Nayati Multi Super Speciality Hospital, Mathura, India. Data of 62 histopathologically proven cancer patients between Nov 2016 and July 2018, were analyzed. This pilot study was conducted to assess the QOL and stress levels of cancer patients by using scales of WHOQOL-BREF, QSC-R23 and Hamilton scale. Results: Among 62 cancer patients, high distress along with poor QOL was seen maximum in males, 40-60 year age group and educated. In majority of domains, high distress was found in middle class, whereas poor QOL was found in Lower class in Environmental domain (p<0.01). We found higher distress in nuclear families (p<0.05). High distress was seen in cancer patients who were aware of illness and was found to statistically significant. Poor QOL in stage 4 was found to be statistically significant in Psychological domain of WHOQOL-BREF. High distress was found in patients undergoing treatment in all patients as compared to Pre-treatment phase and Post-treatment phase (p<0.05). Conclusion: To assess psychological stress in cancer patients using all three scales we could not obtain a conclusive result covering all dimensions of QOL. So, in our next study authors plan to develop one indigenous new scale.